CORRELATION BETWEEN SEVERE MALNUTRITION AND PNEUMONIA AMONG UNDER-FIVE CHILDREN IN EAST JAVA - Nurvita Ruwandasari (Universitas Airlangga, 2019)
Background: East Java Province is the second highest province with pneumonia cases among under-five children totalling 69.17% of all the discovery target of pneumonia cases in 2016. One factor causing pneumonia is severe malnutrition (nutritional status with body weight index according to age which is equal to Zscore < -3 SD). Purpose: This study is aimed at analyzing the correlation between severe malnutrition number and pneumonia cases among under five-year old children per regency/city in East Java. Methods: This type of research was an analytical observational study using a population correlational design. This study used the total population of the number of pneumonia cases and severe malnutrition cases among under five-year old children from all regencies/cities in East Java in 2015-2017. The test used was the Kolmogorov-Smirnov test as a data normality test and Spearman's correlation test to determine whether there was a correlation. Results: This study showed a positive correlation between the number of severe malnutrition and the number of pneumonia cases among under five-year old children per regency/city in East Java (p = < 0.01, p < 0.05) with a moderate correlation (Spearman's correlation = 0.41). Conclusion: The number of severe malnutrition cases has a positive correlation with the number of pneumonia cases among under five-year old children per regency/city in East Java in 2015-2017. Effective countermeasures of severe malnutrition are likely to help reduce the number of pneumonia cases among children under five years of age per regency/city in East Java.